1. In order to determine the best method for solving the equations, we would need to see the equations that are given. Without the equations, it is not possible to determine the best method for solving them.
2. To get the x variables to cancel out, you can either add or subtract the equations, depending on their arrangement. By adding the equations, the x variables will cancel each other out.
3. After canceling out the x variables, the top equation will be obtained by adding the two equations.
4. To get the combined equation, you need to align the equations vertically and add the corresponding terms together. This will result in a new equation that combines the terms from both equations.
5. After obtaining the combined equation, you would need to isolate the variable y by solving for it.
6. Similarly, after obtaining the combined equation, you would need to isolate the variable x by solving for it.
Please provide the specific equations for a more accurate explanation.
1. Choose the best method to solve by looking at the way the equations are set up for you: Response area 2. Using the best method, how could you get the x variables to cancel out? Response area 3. After you complete step 2, what would your top equation be? Response area 4. Line them up and add the equations together to get this equation. Response area 5. Solve for y. Response area 6. Solve for x. Response area Choose a method Operation to get the x variables to cancel Simplified top equation After adding the equations Solve for x and y
18 answers
3x +4y = 48
6x + 2y =60
6x + 2y =60
1. Based on the given equations, we can see that the coefficients of the x variable in both equations are not opposites, so the method of elimination may not be the best approach. The coefficients of the y variable in both equations are also not 1 or -1, so the method of substitution may not be the most efficient method either. In this case, we can use the method of substitution or the method of elimination, as both methods are applicable.
2. To cancel out the x variables using the method of elimination, we can multiply the two equations by suitable numbers so that the coefficients of the x variables become opposites. In this case, we can multiply the second equation by 2 to make the coefficients of the x variables in both equations cancel each other:
Original equations:
3x + 4y = 48
6x + 2y = 60
Multiply the second equation by 2:
12x + 4y = 120
Now, we have two equations with opposite coefficients for the x variables:
3x + 4y = 48
12x + 4y = 120
3. After applying the method of elimination, the top equation will be the simplified equation obtained by adding or subtracting the two equations. Here, let's subtract the first equation from the second equation:
12x + 4y - (3x + 4y) = 120 - 48
9x = 72
The simplified top equation is:
9x = 72
4. Line up the equations and add them together to get a new equation:
Original equations:
3x + 4y = 48
12x + 4y = 120
Lining up the equations:
3x + 4y = 48
12x + 4y = 120
Adding the equations:
3x + 4y + 12x + 4y = 48 + 120
15x + 8y = 168
The combined equation is:
15x + 8y = 168
5. To solve for y, we need to isolate the variable y in the combined equation. Let's rearrange the equation:
15x + 8y = 168
8y = 168 - 15x
y = (168 - 15x)/8
6. To solve for x, we can substitute the value of y from the previous step into any of the original equations. Let's substitute it into the first equation:
3x + 4((168 - 15x)/8) = 48
Solving this equation will give us the value of x.
2. To cancel out the x variables using the method of elimination, we can multiply the two equations by suitable numbers so that the coefficients of the x variables become opposites. In this case, we can multiply the second equation by 2 to make the coefficients of the x variables in both equations cancel each other:
Original equations:
3x + 4y = 48
6x + 2y = 60
Multiply the second equation by 2:
12x + 4y = 120
Now, we have two equations with opposite coefficients for the x variables:
3x + 4y = 48
12x + 4y = 120
3. After applying the method of elimination, the top equation will be the simplified equation obtained by adding or subtracting the two equations. Here, let's subtract the first equation from the second equation:
12x + 4y - (3x + 4y) = 120 - 48
9x = 72
The simplified top equation is:
9x = 72
4. Line up the equations and add them together to get a new equation:
Original equations:
3x + 4y = 48
12x + 4y = 120
Lining up the equations:
3x + 4y = 48
12x + 4y = 120
Adding the equations:
3x + 4y + 12x + 4y = 48 + 120
15x + 8y = 168
The combined equation is:
15x + 8y = 168
5. To solve for y, we need to isolate the variable y in the combined equation. Let's rearrange the equation:
15x + 8y = 168
8y = 168 - 15x
y = (168 - 15x)/8
6. To solve for x, we can substitute the value of y from the previous step into any of the original equations. Let's substitute it into the first equation:
3x + 4((168 - 15x)/8) = 48
Solving this equation will give us the value of x.
where does After you complete step 2, what would your top equation be? Response area 4. Line them up and add the equations together to get this equation. Response area 5. Solve for y. Response area 6. Solve for x. Response area Choose a method Operation to get the x variables to cancel Simplified top equation After adding the equations Solve for x and y come in at?
Apologies for the confusion. Here's the breakdown:
1. Choose a method: This is the step where you analyze the equations and determine which method to use based on their structure.
2. Operation to get the x variables to cancel: This is where you perform an operation (such as adding, subtracting, or multiplying) on the equations to manipulate them so that the x variables cancel each other out.
3. Simplified top equation: After completing step 2, the top equation will be obtained by adding or subtracting the modified equations, resulting in a simplified equation that eliminates the x variable.
4. Line them up and add the equations together to get this equation: This step involves aligning the modified equations and adding the corresponding terms together to obtain a new equation that combines the terms from both equations.
5. Solve for y: Once you have the combined equation from step 4, you isolate the y variable by performing further algebraic operations to solve for its value.
6. Solve for x: After obtaining the value of y, you substitute it back into one of the original equations and solve for x by performing the necessary algebraic operations.
To summarize:
2. Operation to get the x variables to cancel
3. Simplified top equation
4. Line them up and add the equations together to get this equation
5. Solve for y
6. Solve for x
1. Choose a method: This is the step where you analyze the equations and determine which method to use based on their structure.
2. Operation to get the x variables to cancel: This is where you perform an operation (such as adding, subtracting, or multiplying) on the equations to manipulate them so that the x variables cancel each other out.
3. Simplified top equation: After completing step 2, the top equation will be obtained by adding or subtracting the modified equations, resulting in a simplified equation that eliminates the x variable.
4. Line them up and add the equations together to get this equation: This step involves aligning the modified equations and adding the corresponding terms together to obtain a new equation that combines the terms from both equations.
5. Solve for y: Once you have the combined equation from step 4, you isolate the y variable by performing further algebraic operations to solve for its value.
6. Solve for x: After obtaining the value of y, you substitute it back into one of the original equations and solve for x by performing the necessary algebraic operations.
To summarize:
2. Operation to get the x variables to cancel
3. Simplified top equation
4. Line them up and add the equations together to get this equation
5. Solve for y
6. Solve for x
ok now just put
1 the method of elimination
2. Operation to get the x variables to cancel
3. Simplified top equation
4. Line them up and add the equations together to get this equation
5. Solve for y
6. Solve for x
but just the answers for 3x +4y = 48
6x + 2y =60
1 the method of elimination
2. Operation to get the x variables to cancel
3. Simplified top equation
4. Line them up and add the equations together to get this equation
5. Solve for y
6. Solve for x
but just the answers for 3x +4y = 48
6x + 2y =60
Sure! Let's go through the steps for the given equations:
1. The method of elimination is the most suitable method since the coefficients of the x variable are not opposites.
2. To get the x variables to cancel using the method of elimination, we can multiply the first equation by 2 and the second equation by -3:
Original equations:
3x + 4y = 48
6x + 2y = 60
Multiply the first equation by 2:
6x + 8y = 96
Multiply the second equation by -3:
-18x - 6y = -180
3. After completing step 2, the top equation (simplified equation obtained by subtracting or adding the modified equations) would be:
Top equation (after subtracting the second equation from the first equation):
24y = 276
4. Line up the equations and add them together to get a combined equation:
Lining up the equations:
6x + 8y = 96
-18x - 6y = -180
Adding the equations:
-12x + 2y = -84
Combined equation:
-12x + 2y = -84
5. To solve for y, we need to isolate the variable y in the combined equation. Let's rearrange the equation:
-12x + 2y = -84
2y = 12x - 84
y = (12x - 84)/2
y = 6x - 42
6. To solve for x, we substitute the value of y back into any of the original equations. Let's substitute it in the first equation:
3x + 4(6x - 42) = 48
Simplifying this equation will give us the value of x.
Please note that since the equations are not provided, we are assuming that the above equations are the ones you are referring to.
1. The method of elimination is the most suitable method since the coefficients of the x variable are not opposites.
2. To get the x variables to cancel using the method of elimination, we can multiply the first equation by 2 and the second equation by -3:
Original equations:
3x + 4y = 48
6x + 2y = 60
Multiply the first equation by 2:
6x + 8y = 96
Multiply the second equation by -3:
-18x - 6y = -180
3. After completing step 2, the top equation (simplified equation obtained by subtracting or adding the modified equations) would be:
Top equation (after subtracting the second equation from the first equation):
24y = 276
4. Line up the equations and add them together to get a combined equation:
Lining up the equations:
6x + 8y = 96
-18x - 6y = -180
Adding the equations:
-12x + 2y = -84
Combined equation:
-12x + 2y = -84
5. To solve for y, we need to isolate the variable y in the combined equation. Let's rearrange the equation:
-12x + 2y = -84
2y = 12x - 84
y = (12x - 84)/2
y = 6x - 42
6. To solve for x, we substitute the value of y back into any of the original equations. Let's substitute it in the first equation:
3x + 4(6x - 42) = 48
Simplifying this equation will give us the value of x.
Please note that since the equations are not provided, we are assuming that the above equations are the ones you are referring to.
2. Operation to get the x variables to cancel mutiply the top equation x -2, mutiply the top equation x 2, dived the top equation by 4, divied the bottom eqation by 2
3. Simplified top equation
x + 2y = 46, 3x+ y = 30, -6x - 8y = -96, -6x +4y = 96
4. Line them up and add the equations together to get this equation(after adding the equations)
-6y=36, 6y=-96, -8y=-96, 8y = 96
5. Solve for y
y=6, y=18, y=-12
6. Solve for x
x=-3, x=8, x=6
3. Simplified top equation
x + 2y = 46, 3x+ y = 30, -6x - 8y = -96, -6x +4y = 96
4. Line them up and add the equations together to get this equation(after adding the equations)
-6y=36, 6y=-96, -8y=-96, 8y = 96
5. Solve for y
y=6, y=18, y=-12
6. Solve for x
x=-3, x=8, x=6
Based on the given operations and equations, let's update the step-by-step breakdown:
2. Operation to get the x variables to cancel:
The given operations are not clear and may have resulted in incorrect values for the equations. Please provide the specific operations performed to cancel the x variables, and I will adjust the subsequent steps accordingly.
3. Simplified top equation:
Without the clear operations provided, it is not possible to determine the simplified top equation accurately. Once the correct operations are provided, I will be able to simplify the equations and determine the top equation.
4. Line them up and add the equations together to get this equation:
Since the equations have not been properly simplified, it is not possible to accurately line them up and add them together.
5. Solve for y:
The values for y that have been provided (y = 6, y = 18, y = -12) are based on incorrect simplifications and are not accurate. Please provide the correct simplified top equation, and I will be able to determine the correct value for y.
6. Solve for x:
Similarly, the values for x that have been provided (x = -3, x = 8, x = 6) are based on incorrect simplifications. Once the correct simplified top equation is provided, I will be able to solve for x accurately.
Please provide the correct operations performed to cancel the x variables, and I will adjust the steps and provide the accurate solutions.
2. Operation to get the x variables to cancel:
The given operations are not clear and may have resulted in incorrect values for the equations. Please provide the specific operations performed to cancel the x variables, and I will adjust the subsequent steps accordingly.
3. Simplified top equation:
Without the clear operations provided, it is not possible to determine the simplified top equation accurately. Once the correct operations are provided, I will be able to simplify the equations and determine the top equation.
4. Line them up and add the equations together to get this equation:
Since the equations have not been properly simplified, it is not possible to accurately line them up and add them together.
5. Solve for y:
The values for y that have been provided (y = 6, y = 18, y = -12) are based on incorrect simplifications and are not accurate. Please provide the correct simplified top equation, and I will be able to determine the correct value for y.
6. Solve for x:
Similarly, the values for x that have been provided (x = -3, x = 8, x = 6) are based on incorrect simplifications. Once the correct simplified top equation is provided, I will be able to solve for x accurately.
Please provide the correct operations performed to cancel the x variables, and I will adjust the steps and provide the accurate solutions.
those are the opsens u pick the rigth ansewr for the equation
3x +4y = 48
6x + 2y =60
3x +4y = 48
6x + 2y =60
Apologies for the confusion. Based on the given equations, let's go through the steps again:
1. Choose the method: Since the coefficients of the x variable are not opposites, we will use the method of multiplication to get the x variables to cancel.
2. Operation to get the x variables to cancel: Multiply the top equation by -2 and the bottom equation by 3:
Original equations:
3x + 4y = 48
6x + 2y = 60
Multiply the top equation by -2:
-6x - 8y = -96
Multiply the bottom equation by 3:
18x + 6y = 180
3. Simplified top equation: After multiplying the equations, the top equation becomes:
Top equation (after subtracting the modified equations):
-6x - 8y = -96
4. Line them up and add the equations together to get a combined equation:
Lining up the equations:
-6x - 8y = -96
18x + 6y = 180
Adding the equations:
12x - 2y = 84
Combined equation:
12x - 2y = 84
5. Solve for y: To isolate the y variable, rearrange the equation:
12x - 2y = 84
-2y = -12x + 84
y = (12x - 84)/(-2)
y = -6x + 42
6. Solve for x: Substitute the value of y into one of the original equations. Let's substitute it into the first equation:
3x + 4(-6x + 42) = 48
Solving this equation will give us the value of x.
Please provide the specific operations performed if the given equations and steps do not match what you intended.
1. Choose the method: Since the coefficients of the x variable are not opposites, we will use the method of multiplication to get the x variables to cancel.
2. Operation to get the x variables to cancel: Multiply the top equation by -2 and the bottom equation by 3:
Original equations:
3x + 4y = 48
6x + 2y = 60
Multiply the top equation by -2:
-6x - 8y = -96
Multiply the bottom equation by 3:
18x + 6y = 180
3. Simplified top equation: After multiplying the equations, the top equation becomes:
Top equation (after subtracting the modified equations):
-6x - 8y = -96
4. Line them up and add the equations together to get a combined equation:
Lining up the equations:
-6x - 8y = -96
18x + 6y = 180
Adding the equations:
12x - 2y = 84
Combined equation:
12x - 2y = 84
5. Solve for y: To isolate the y variable, rearrange the equation:
12x - 2y = 84
-2y = -12x + 84
y = (12x - 84)/(-2)
y = -6x + 42
6. Solve for x: Substitute the value of y into one of the original equations. Let's substitute it into the first equation:
3x + 4(-6x + 42) = 48
Solving this equation will give us the value of x.
Please provide the specific operations performed if the given equations and steps do not match what you intended.
USE THE METOED OF ELIMINATION ND DO IT RIGHT WITH THE CORRECT ANESEWS NOW
Apologies for the confusion earlier. Let's solve the given equations using the method of elimination correctly:
1. Given equations:
3x + 4y = 48
6x + 2y = 60
2. To cancel out the x variables, multiply the first equation by -2 and the second equation by 1:
Multiply the first equation by -2:
-6x - 8y = -96
Second equation remains the same:
6x + 2y = 60
3. Add the modified equations to eliminate the x variables:
-6x - 8y + 6x + 2y = -96 + 60
-6y = -36
4. Simplified equation after adding:
-6y = -36
5. Solve for y: Divide both sides of the equation by -6:
y = 6
6. Substitute the value of y in either of the original equations to solve for x. Let's use the first equation:
3x + 4(6) = 48
3x + 24 = 48
3x = 24
x = 8
Therefore, the solution to the system of equations is x = 8 and y = 6.
1. Given equations:
3x + 4y = 48
6x + 2y = 60
2. To cancel out the x variables, multiply the first equation by -2 and the second equation by 1:
Multiply the first equation by -2:
-6x - 8y = -96
Second equation remains the same:
6x + 2y = 60
3. Add the modified equations to eliminate the x variables:
-6x - 8y + 6x + 2y = -96 + 60
-6y = -36
4. Simplified equation after adding:
-6y = -36
5. Solve for y: Divide both sides of the equation by -6:
y = 6
6. Substitute the value of y in either of the original equations to solve for x. Let's use the first equation:
3x + 4(6) = 48
3x + 24 = 48
3x = 24
x = 8
Therefore, the solution to the system of equations is x = 8 and y = 6.
R THESE RIGHT?????
Apologies for any confusion caused. I made an error in the previous response. Let's solve the given equations correctly using the method of elimination:
1. Given equations:
3x + 4y = 48
6x + 2y = 60
2. Multiply the first equation by 2 and the second equation by -3 to eliminate the x variables:
(2)(3x + 4y) = (2)(48) -> 6x + 8y = 96
(-3)(6x + 2y) = (-3)(60) -> -18x - 6y = -180
The modified equations are:
6x + 8y = 96
-18x - 6y = -180
3. Add the modified equations:
(6x + 8y) + (-18x - 6y) = 96 + (-180)
-12x + 2y = -84
4. Simplified equation after adding:
-12x + 2y = -84
5. Solve for y: Isolate the y variable:
2y = 12x - 84
y = (12x - 84) / 2
y = 6x - 42
6. Substitute the value of y into either of the original equations to solve for x. Let's use the first equation:
3x + 4(6x - 42) = 48
3x + 24x - 168 = 48
27x - 168 = 48
27x = 216
x = 8
Therefore, the correct solution to the system of equations is x = 8 and y = 6.
1. Given equations:
3x + 4y = 48
6x + 2y = 60
2. Multiply the first equation by 2 and the second equation by -3 to eliminate the x variables:
(2)(3x + 4y) = (2)(48) -> 6x + 8y = 96
(-3)(6x + 2y) = (-3)(60) -> -18x - 6y = -180
The modified equations are:
6x + 8y = 96
-18x - 6y = -180
3. Add the modified equations:
(6x + 8y) + (-18x - 6y) = 96 + (-180)
-12x + 2y = -84
4. Simplified equation after adding:
-12x + 2y = -84
5. Solve for y: Isolate the y variable:
2y = 12x - 84
y = (12x - 84) / 2
y = 6x - 42
6. Substitute the value of y into either of the original equations to solve for x. Let's use the first equation:
3x + 4(6x - 42) = 48
3x + 24x - 168 = 48
27x - 168 = 48
27x = 216
x = 8
Therefore, the correct solution to the system of equations is x = 8 and y = 6.
I hate u
I apologize if there was any confusion or frustration caused. If there is anything specific you are struggling with or would like assistance with, please let me know and I'll do my best to help.
I gave u the ansewrs option and u didnt use them they are
1 choose a method
(substitution, graphing, elimination)
2. Operation to get the x variables to cancel
( mutiply the top equation x -2, mutiply the top equation x 2, dived the top equation by 4, divied the bottom eqation by 2)
3. Simplified top equation
(x + 2y = 46, 3x+ y = 30, -6x - 8y = -96, -6x +4y = 96)
4. Line them up and add the equations together to get this equation(after adding the equations)
(-6y=36, 6y=-96, -8y=-96, 8y = 96)
5. Solve for y
(y=6, y=18, y=-12)
6. Solve for x
(x=-3, x=8, x=6)
1 choose a method
(substitution, graphing, elimination)
2. Operation to get the x variables to cancel
( mutiply the top equation x -2, mutiply the top equation x 2, dived the top equation by 4, divied the bottom eqation by 2)
3. Simplified top equation
(x + 2y = 46, 3x+ y = 30, -6x - 8y = -96, -6x +4y = 96)
4. Line them up and add the equations together to get this equation(after adding the equations)
(-6y=36, 6y=-96, -8y=-96, 8y = 96)
5. Solve for y
(y=6, y=18, y=-12)
6. Solve for x
(x=-3, x=8, x=6)